Parental Impact on Attitude Formation - A Siblings Study on Worries about Immigration - Jan Brenner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
The existing literature on attitudes towards immigration has not accounted for the potential effect of unobservable home education on attitude formation. Yet, factors such as parents' knowledge, their morals, and their weltanschauung are likely to influence the attitudes of the next generation.Their omission from the analysis thus threatens to lead to erroneous conclusions. Utilizing siblings data from the German Socio-Economic Panel (GSOEP) this paper analyzes the determinants of worries about immigration controlling for unobserved family specific effects.Our results suggest that benchmark models used in the literature yield inconsistent estimates of the main determinants of attitudes towards immigration.
Keywords: C51; F22; J15; 330; Subjective data; siblings data; unobserved effects; minorities; Einwanderung; Ausländer; Meinung; Eltern; Weltanschauung; Schätzung; Deutschland